Overcoming adversarial obstacles in problem solving - Navarro, Soledad V. (2009)
This study aimed to determine the how six practitioners from the clusters of economics, social sciences, and health services, enumerated in the UP General Catalogue of 2002 do problem solving. The constructivist-interpretative approach was employed in the study. In-depth interviews and observation reports, case studies, life history, experiences, and other empirical materials served as the major sources of data. It was found that all practitioners had more or less the same understanding about problems and problem-solving and follow the same procedure but not strictly the same sequence. These problem solving approaches and strategies may be traced to universal factors in psychology and education. Personal family, education, and work histories are major elements in individual problem solving.
Thesis (Ph.D. Educational Psychology)--University of the Philippines, Diliman.
Keywords: Problem solving; Business; Teaching -- Philippines; Medicine -- Philippines; Professional employees -- Philippines